RIGHT TO LEGAL AID IN EUROPE - Limantė, Agnė; Limantas, Manfredas (Teisė, 2016)
The article analyses regulation of the right to legal aid in international and EU law. Particular attention is paid to the search of legal aid quality standards in Europe, their overview and critical assesment.